2019
DOI: 10.1101/616813
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and Determinants of Caesarean Section in South and South-east Asian Women

Abstract: Background: Caesarean section is considered a preferable and safe method of delivery. In the last decade, its prevalence has increased in both developed and developing countries. In the context of developing countries viz., South Asia (the highest populated region) and South-east Asia (the third highest populated region), the preference for, and variation in, caesarean section delivery and its associated maternal socioeconomic characteristics are still to be determined.Objective: To study the magnitude of caes… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 18 publications
(13 reference statements)
3
14
0
1
Order By: Relevance
“…For example, Poudel et al (2020) 17 reported that the pooled stillbirth rate in India, Bangladesh, Nepal and Pakistan was 25.15 per 1,000 births. Another study reported that, the prevalence of C‐section delivery is around 13% in South Asian countries 19 . Although several studies have pointed the association between GDM and adverse pregnancy outcomes, it is important that these findings are synthesized systematically to provide concrete evidence for policymakers and practitioners in South Asia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Poudel et al (2020) 17 reported that the pooled stillbirth rate in India, Bangladesh, Nepal and Pakistan was 25.15 per 1,000 births. Another study reported that, the prevalence of C‐section delivery is around 13% in South Asian countries 19 . Although several studies have pointed the association between GDM and adverse pregnancy outcomes, it is important that these findings are synthesized systematically to provide concrete evidence for policymakers and practitioners in South Asia.…”
Section: Introductionmentioning
confidence: 99%
“…Another study reported that, the prevalence of C-section delivery is around 13% in South Asian countries. 19 Although several studies have pointed the association between GDM and adverse pregnancy outcomes, it is important that these findings are synthesized systematically to provide concrete evidence for policymakers and practitioners in South Asia. This study aimed to synthesize the evidence on the association between GDM and adverse pregnancy outcomes in South Asian countries.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in Bangladesh [ 17 ], the CS rate increased eight-fold from 2004 to 2017/8 with a four-fold increase in Nepal [ 12 , 18 ] between 2001 and 2011, with this trend continuing [ 12 , 17 - 18 ]. Previous studies found that CS delivery was higher among urban women, primarily educated women, than rural, uneducated women [ 9 , 11 , 18 - 22 ]. As the rate of CS delivery in private hospitals was significantly higher than in government hospitals among South and Southeast Asian women, only women from wealthy groups could afford the high cost and quickly decided for CS [ 9 , 23 - 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found that CS delivery was higher among urban women, primarily educated women, than rural, uneducated women [ 9 , 11 , 18 - 22 ]. As the rate of CS delivery in private hospitals was significantly higher than in government hospitals among South and Southeast Asian women, only women from wealthy groups could afford the high cost and quickly decided for CS [ 9 , 23 - 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation